Choreito, a Kampo medicine attenuates detrusor overactivity and bladder pain symptoms in rat tranilast‐induced interstitial cystitis/bladder pain syndrome‐like model. Issue 1 (15th November 2022) - Tokita, Yohei; Sugaya, Kimio; Nishijima, Saori; Tsuchiya, Naoko; Hamaguchi, Marie; Yamamoto, Hideyuki
Abstract: Aims: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic inflammatory condition of the bladder. However, there are only a few medicines that are of pharmaceutical grade and reliably effective for IC/BPS symptoms. Choreito (CRT) is a pharmaceutical‐grade Kampo medicine and has been widely prescribed for patients of lower urinary tract symptoms (LUTS) and BPS in Japan. In this study, we exploratory investigated the effects of CRT on the IC/BPS‐like symptoms induced by tranilast. Methods: The rat IC/BPS‐like model was induced by feeding administration with 0.4% tranilast. The rats were divided into the three following treatment groups: normal diet (Normal), tranilast treatment (Control), and the groups of 1% CRT (CRT) treatment for IC/BPS‐like model. After 4 weeks, continuous cystmetry, locomotor, and vascular permeability was assessed. Furthermore, the cytokine levels in bladder were analyzed by the Bio‐Plex suspension array system and plasma monoamine were measured. Results: Control group exhibited 14.3% decrease of locomotor activity in the dark period, and which were 20.3% increase by 1%CRT treatment. The voiding interval was shorter in control than in other groups. 1%CRT suppressed the shortening of voiding interval. Evans blue leakage of bladder wall observed 44.8% higher in control group than in the normal group. The leakage of 1%CRT group was 33.3% less than in the control group. The cytokine level of IFNγ and VEGF were elevated in the control, and CRT treatment suppressed the elevation of IFNγ in the bladder. Plasma noradrenaline was significantly reduced by CRT treatment compared normal group. Conclusion: These results suggest that CRT can be an effective therapeutic agent for the treatment of IC/BPS‐like symptoms.